2013
DOI: 10.1152/ajprenal.00401.2012
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effects of angiotensin-(1–7) on the NHE3 exchanger and [Ca2+]iin in vivo proximal tubules

Abstract: The acute direct action of angiotensin-(1-7) [ANG-(1-7)] on bicarbonate reabsorption (JHCO(3)(-)) was evaluated by stationary microperfusions on in vivo middle proximal tubules in rats using H ion-sensitive microelectrodes. The control JHCO(3)(-) is 2.82 ± 0.078 nmol·cm(-2)·s(-1) (50). ANG-(1-7) (10(-12) or 10(-9) M) in luminally perfused tubules decreases JHCO(3)(-) (36 or 60%, respectively), but ANG-(1-7) (10(-6) M) increases it (80%). A779 increases JHCO(3)(-) (30%) and prevents both the inhibitory and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…It is worth noting that both studies demonstrate that the Ang-(1-7)/Mas antagonist DAL blocked the cellular actions of Ang-(1-7) suggesting the Mas receptor may transduce dose-dependent effects of the peptide. In this regard, de Mello-Aires and colleagues reported dose-dependent biphasic effects of Ang-(1-7) on the proximal tubule NHE3 exchanger that were completely blocked by DAL (8). Ang II also exhibits biphasic effects on sodium reabsorption that are mediated through the AT 1 receptor and multiple signaling pathways, albeit the tubular actions of Ang II are opposite to those of Ang-(1-7) (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that both studies demonstrate that the Ang-(1-7)/Mas antagonist DAL blocked the cellular actions of Ang-(1-7) suggesting the Mas receptor may transduce dose-dependent effects of the peptide. In this regard, de Mello-Aires and colleagues reported dose-dependent biphasic effects of Ang-(1-7) on the proximal tubule NHE3 exchanger that were completely blocked by DAL (8). Ang II also exhibits biphasic effects on sodium reabsorption that are mediated through the AT 1 receptor and multiple signaling pathways, albeit the tubular actions of Ang II are opposite to those of Ang-(1-7) (22).…”
Section: Discussionmentioning
confidence: 99%
“…Functional links between AGEs, TGF-β and the differential activation of the renal RAS are becoming increasingly evident as well (48). Cao and colleagues find that AGEs (hydoxychloride-treated rat albumin) increased the expression of the precursor protein angiotensinogen, ACE and AT 1 receptors in the NRK-52E cells (8). Chou et al also reported that chronic treatment of NRK-52E cells with high glucose or TGF-β reduced the mRNA and protein expression of ACE2 and the Ang-(1-7)/Mas receptor (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diuretic/natriuretic effects of Ang-(1-7) may also be due to the regulation of Na + reabsorption within the proximal tubule. In vivo and in vitro studies showed that Ang-(1-7) is a potent inhibitor of Na + reabsorption in this nephron segment, acting on different receptors [46][47][48][49] . Ang-(1-7) can bind to distinct receptors and induces different cellular responses depending on the cell type.…”
Section: New Members Of Ras: Ang Ii-derived Peptidesmentioning
confidence: 97%
“…For instance, in distal tubule cell (MDCK), Ang-(1-7) inhibits (Na + + K + )-ATPase activity through the AT1 receptor to stimulate the PI-PLC/PKC signaling pathway [47] , whereas in the proximal tubule, it inhibits Na + -ATPase via the AT2/G(i/o) protein/cGMP/PKG pathway [48] . Moreover, at different concentrations of Ang-(1-7) (10 -12 , 10 -9 , or 10 -6 mol/L) used in intratubular perfusion in the absence or presence of the Mas receptor antagonist (A779) of rat isolated proximal tubules, it was shown that Ang-(1-7) has a biphasic dose-dependent effect on the Na + /H + exchanger mediated by Mas receptor and gave a moderate increase in intracellular Ca 2+ levels ([Ca 2+ ]i) [49] . Increased [Ca 2+ ]i stimulated by Ang-(1-7) also occurred in MDCK cells, but through the AT1 receptor, which in turn stimulated Ca 2+ release from endoplasmic reticulum via the PLC pathway and Ca 2+ influx through PLA2-dependent store-operated Ca 2+ entry [24] .…”
Section: New Members Of Ras: Ang Ii-derived Peptidesmentioning
confidence: 99%